Hercules Toxicants for Sprays and Powders - Hercules Incorporated (1947 Hercules Advertisements, 1947)
Advertisement for Thanite and other toxicants manufactured and sold by the Hercules Powder Company for use in pesticides and insecticides. This advertisement appeared in the April, May, and June 1947 issues of Chemical Industries. Formed in 1912 as part of an anti-trust settlement with DuPont, the Hercules Powder Company (later Hercules Inc.) initially specialized in the manufacture of explosives and smokeless powders and subsequently diversified its business to encompass a variety of industrial products, including pine and paper chemicals, synthetics, pigments, polymers, and cellulose.
Keywords: Chemical industry; Hercules Incorporated; DDT (Insecticide); Corporations; Naval stores; Thanite; Insecticides; Advertising, Industrial